1999
DOI: 10.1093/nar/27.10.2108
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of the third subunit of mammalian DNA polymerase   by PCNA-affinity chromatography of mouse FM3A cell extracts

Abstract: Using proliferating cell nuclear antigen affinity chroma-tography and glycerol gradient centrifugation of partially purified fractions from mouse FM3A cells we have been able to isolate novel complexes of DNA polymerase delta and DNA ligase 1 containing clearly defined subunit compositions. In addition to the well known catalytic subunit of 125 kDa and accessory subunit of 48 kDa, the DNA polymerase delta complex contained three supplementary components, one of which reacted with antibodies directed against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 35 publications
4
76
0
Order By: Relevance
“…However, PDIP1 shares only 20% identity with the mouse homolog of the pol ␦ third subunit, p66 (14), and does not appear to be an integral component of pol ␦ because it does not copurify with the enzyme from calf thymus (unpublished observation). Thus, PDIP1 is unlikely to be a homolog of Cdc27.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, PDIP1 shares only 20% identity with the mouse homolog of the pol ␦ third subunit, p66 (14), and does not appear to be an integral component of pol ␦ because it does not copurify with the enzyme from calf thymus (unpublished observation). Thus, PDIP1 is unlikely to be a homolog of Cdc27.…”
Section: Discussionmentioning
confidence: 98%
“…It is believed that, in addition to their roles in mediating the interaction of PCNA and pol ␦, both Cdc27 and Pol32 function as dimerization factors for pol ␦, a requirement for concurrent replication of the leading and lagging strands at the replication fork (12,13). A putative third subunit of mammalian pol ␦, p66, has been isolated from mouse (14) and calf thymus tissues (15) by affinity chromatography, but it is not yet clear whether mammalian p66 is functionally analogous to Cdc27 and Pol32.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian Pol d was subsequently shown to be a four-subunit enzyme, Pol d4, by the identification of p68, a homolog of Pol32 [Hughes et al, 1999;Mo et al, 2000], and p12, which possesses limited sequence similarity to Cdm1 . Human Pol d4 is a heterotetramer of p125, p50, p68, and p12 subunits, like yPold4 in S. pombe.…”
Section: Introductionmentioning
confidence: 99%
“…Also, p125 subunit interacts with and becomes phosphorylated by cyclin D3/Cdk4 and cyclin E/Cdk2 (Wu et al, 1998), thus suggesting a possible role in S phase checkpoint control. Additionally, p66/68 (Hughes et al, 1999) and p12 were identified as part of the mammalian pold complex. Whereas p66/68 binds PCNA, a specific role for p12 subunit has not been identified, although its addition to an in vitro assay enhances the DNA polymerizing activity of the enzyme (Podust et al, 2002).…”
mentioning
confidence: 99%